Discharging accountability through governance: Cases from waqf institutions in Indonesia - Nathasa Mazna Ramli; Nurul Aini Muhamed; Nurul Husna Mohd Salleh (Academy of Islamic Studies, University of Malaya, 2024)
Vol. 2 No. 1(page: 1-13)